A 1997 Social Accounting Matrix for Colombia - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1997 Social Acounting Matrix (SAM) for Colombia has an activities-commodities structure, characterized by 60 sectors and commodities; ten households; seven types of labor factors; 26 types of taxes and subsidies on production, 22 tax ranges and subsidies on products; one category for direct income taxes and another category entitled other taxes. In particular, the documentation contains a full description of the Micro SAM for Colombia explaining the procedure implemented for the dissagregation of taxes, the dissagregation of the production and commodity accounts and the dissagregation of employment.